Integrity Content in the Selection of High-Level Leadership Positions (JPT) as a Determinant of Success in Providing the Best Service to the Public (Public Sector Human Resources Practices) - maisondra maisondra (Post Graduate School of Government Science, 2025)
This study discusses the importance of integrity in the selection of High-Level Leadership Positions (Jabatan Pimpinan Tinggi – JPT) in Indonesia and the challenges faced in implementing a merit-based selection system. The selection system for officials has evolved from the colonial era to the Reform Era, where the government now applies an open selection process to ensure transparency and accountability. However, various issues such as political interference, collusion, and nepotism remain obstacles to producing officials with high integrity. This research employs a qualitative approach using a case study method to analyze the implementation of the JPT selection process in Indonesia. Data was obtained through interviews with civil servants, members of the State Civil Apparatus Commission (Komisi Aparatur Sipil Negara – KASN), academics, and direct observations of the selection process. The findings reveal that, despite the implementation of open selection policies, there are still weaknesses in enforcing transparency principles, monitoring the selection process, and applying integrity values in the recruitment system. As a recommendation, this study emphasizes the need for improvements in the selection system by strengthening integrity standards, enhancing the independence of selection committees, conducting thorough background checks on candidates, and increasing public oversight. The implementation of talent management is also proposed as a strategic solution to ensure the sustainability of high-quality leadership. Thus, enhancing integrity in JPT selection can contribute to improving public service quality and strengthening public trust in the government